Effects of drought stress on some agronomic and bio-physiological traits of Trtiticum aestivum, Triticale, and Tritipyrum genotypes - Shanazari, Mahdi; Golkar, Pooran; Mirmohammady Maibody, Ali Mohammad (My University, 2018)
Drought tolerance is a complex trait that involves different biochemical and physiological mechanisms in plants. It was the objective of the present study to evaluate the agronomic and biochemical responses of triticale, tritipyrum, and wheat to drought stress. For this purpose, twenty-seven genotypes were evaluated under two levels (non-stress and drought stress) of irrigation during 2015‒2017. The metabolic traits studied included relative water content (RWC), membrane stability index (MSI), chlorophyll a (Chla), chlorophyll b (Chlb), carotenoids (Car), leaf proline content (Pro), leaf soluble carbohydrates (LSC), glycine betaine (GB), malondialdehyde (MDA), hydrogen peroxide (H2O2), seeds per spike (SS), seed weight (SW), biological yield (BY) and seed yield (SY). Drought stress increased Pro, LSC, and GB contents as well as lipid peroxidation through increasing MDA and H2O2 activities. However, both RWC and MSI indices as well as SS, SW, SY and BY reduced as a result of drought treatment although the least decrease of SY was observed at triticale group. During the two years of study, the tritipyrum genotypes exhibited their drought tolerance by accumulation of more LSC and GB as well as lower decrease in SW while the triticale ones responded by maintaining higher levels of RWC but producing less MDA and H2O2. It may, therefore, be concluded that the three species studied exploit different mechanisms to maintain tolerance against drought stress. Finally, correlation analysis indicated the positive effects of LSC on SY under both drought and normal conditions, which is obviously a promising trait in wheat, triticale, and tritipyrum that can be beneficially exploited in drought tolerance improvement programs
Keywords: Bread wheat; biplot; drought tolerance; glycine betaine; malondialdehyde